P2X7 Receptor-Related Genetic Mouse Models – Tools for Translational Research in Psychiatry - Urbina-Treviño, Lidia; von Mücke-Heim, Iven-Alex; Deussing, Jan M. (Frontiers in Neural Circuits, 2022)
Depression is a common psychiatric disorder and the leading cause of disability worldwide. Although treatments are available, only about 60% of treated patients experience a significant improvement in disease symptoms. Numerous clinical and rodent studies have identified the purinergic P2X7 receptor (P2X7R) as one of the genetic factors potentially contributing to the disease risk. In this respect, genetically engineered mouse models targeting the P2X7R have become increasingly important in studying designated immunological features and subtypes of depression in vivo. This review provides an overview of the P2X7R-related mouse lines currently available for translational psychiatric research and discusses their strengths, weaknesses, and potentials.